Reduction of Tissue Na+ Accumulation After Renal Transplantation - Dahlmann, Anke; Linz, Peter; Zucker, Isabelle; Haag, Viktor; Jantsch, Jonathan; Dienemann, Thomas; Nagel, Armin Michael; Neubert, Patrick; Rosenhauer, Daniela; Rauh, Manfred; Horn, Stephan; Müller, Dominik N.; et al. (Kidney International Reports, 2021)
Introduction: Chronic kidney disease (CKD) engenders salt-sensitive hypertension. Whether or not tissue Nathorn accumulation is increased in CKD patients remains uncertain. How tissue Nathorn is affected after renal transplantation has not been assessed.
CRIS-Team WoS Importer:2021-10-01